Principles of Teaching and Learning from the Bhagavad Gita: A Thematic Analysis - Calvert, Isaac (Religious education, 2024)
This article explores principles of teaching and learning found within the Bhagavad Gita, a sacred Hindu text. After an in-depth thematic hermeneutic analysis of two translations of the text, we found eight themes, including the disciple’s role: questioning and emulating the Guru; the Guru’s role: teaching as the supreme act of love; learning as Enlightenment; ultimate Self-knowledge as Self-realization; taming the mind through meditation; action superseding inaction in learning; devotion and effort as prerequisites to learning; and detachment from the outcomes of learning. Among our most prominent findings are insights regarding teacher and learner motivation and the centrality of effort to learning. We hope this paper adds to scholarly conversation surrounding the Gita and enriches education philosophy generally.